ASSESSMENT OF SAFETY FACTORS OF ENDURANCE AND THE EQUIVALENT OF DESTROYING THE ABILITY OF CYCLIC STRESSES ACCORDING TO FULL-SCALE TESTING OF ROLLING STOCK - Horobets, V. L. (Science and Transport Progress, 2003)
With the aim of precise definition of endurance margin factors of the rolling-stock carrying structures and calculation of amplitudes of symmetric cycles of their loading, equivalent in their destructibility, a calculation model has been offered, which takes into account the distribution of the loading cycle parameters of the carrying structure in operational conditions.